Методика управління взаємовідносинами з стейкхолдерами як етап системи економічної безпеки підприємства - Ковалевська, А. В.; Кусік, Н. Л. (ХНУРЭ, 2014)
In work importance of inclusion in process of formation of system of economic safety of the enterprise of a stage of management by stakeholders is shown. Such actions are directed on harmonization of interests of the enterprise with the most significant social groups and economic partners. Increase of level of coherence of interests is the real tool to providing high level of economic safety
Keywords: управління взаємовідносинами; економічна безпека підприємства